Պաշտոնական նամակագրությունը և դիվանագիտական ընծաները հայ-մոնղոլական հարաբերություններում - Դանիելյան, Գագիկ (Մատենադարան)
The third part of the article focuses on the diplomatic gifts and presents exchanged between the Mongol and Armenian sovereigns. In this case, our main source of information is Armenian historiography, although a number of interesting reports are also found in Arabic, Persian and Syriac historiographic sources of the time. Третья часть статьи посвящена дарам и подношениям, которыми обменивались монгольские и армянские государи. В данном случае нашими основными источниками информации являются памятники армянской историографии, хотя ряд интересных сообщений встречается также в арабских, персидских и сирийских исторических источниках того времени.
Keywords: Պատմություն